2022
DOI: 10.3389/fpls.2022.1026575
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the role of endophytic microbiome in postharvest diseases management of fruits: Opportunity areas in commercial up-scale production

Abstract: As endophytes are widely distributed in the plant’s internal compartments and despite having enormous potential as a biocontrol agent against postharvest diseases of fruits, the fruit–endophyte–pathogen interactions have not been studied detail. Therefore, this review aims to briefly discuss the colonization patterns of endophytes and pathogens in the host tissue, the diversity and distribution patterns of endophytes in the carposphere of fruits, and host–endophyte–pathogen interactions and the molecular mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 209 publications
0
3
0
Order By: Relevance
“…Our results revealed that the Ascomycota community was the dominant community in ginger tissues, and that Fusarium was the most abundant genus in each tissue. Previous research reports have indicated that the onset of disease can induce the reassembly and functional adaptation of the plant-associated microbiome 22 . For example, Fusarium was the most abundant fungal genus in both healthy and diseased pepper tissues, while Diaporthe, Fusarium, Phomopsis, Plectosphaerella, Stemphylium, and Cryptococcus were the dominant fungi in the root and stem tissues of peppers with symptoms of Fusarium wilt 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Our results revealed that the Ascomycota community was the dominant community in ginger tissues, and that Fusarium was the most abundant genus in each tissue. Previous research reports have indicated that the onset of disease can induce the reassembly and functional adaptation of the plant-associated microbiome 22 . For example, Fusarium was the most abundant fungal genus in both healthy and diseased pepper tissues, while Diaporthe, Fusarium, Phomopsis, Plectosphaerella, Stemphylium, and Cryptococcus were the dominant fungi in the root and stem tissues of peppers with symptoms of Fusarium wilt 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in the laboratory, it is mainly taken as a flat plate to buckle and seal with a sealing film to prevent the volatilization of VOCs and avoid reducing their fungistatic activity [26]. In practical applications, depending on the type of fruits and vegetables and the storage conditions, fumigation can be used to achieve antagonistic effects against pathogenic fungi in a closed environment, such as entire storage rooms and individual transport containers [30]. In this case, endophytic fungi can be cultivated in a separate chamber, and the VOCs produced are released into the storage room via a pump without any direct contact with the fruits and vegetables, preventing infection of the fruits by the strain [40].…”
Section: Application Of Endophytic Fungal Vocs As Postharvest Fruit A...mentioning
confidence: 99%
“…They colonize a wide range of plants and can be isolated from all plant organs, including roots, stems, leaves, flowers, fruits, and seeds [29]. Currently, some fungi with antagonistic effects, such as Trichoderma spp., are used in a large number of applications for controlling fruit and vegetable postharvest diseases, but the application regarding endophytes is very limited [30].…”
Section: Introductionmentioning
confidence: 99%
“…Streptomyces species, a Grampositive bacterium was recently discovered to be able to stop the infection caused by various bacteria and fungi, including Burkholderia glumae, a bacterial rice pathogen (Degrassi and Carpentieri-Pipolo 2020). Notably important tasks are screening microbial antagonists against diverse phytopathogens (Kumari et al, 2022). For BCA screening, bacterial strains that may produce antibiotic or volatile chemicals as well as enzymes that can disrupt or lessen the pathogen virulence factors are favored (Zimand et al,.…”
Section: Managing Root Rot By Endophytic Bacteriamentioning
confidence: 99%
“…For BCA screening, bacterial strains that may produce antibiotic or volatile chemicals as well as enzymes that can disrupt or lessen the pathogen virulence factors are favored (Zimand et al,. 1996;Kapat et al, 1998;Kumari et al, 2022). Table 4 enlists the endophyte-produced bioactive compounds that may be employed to combat biotic infections after harvest.…”
Section: Managing Root Rot By Endophytic Bacteriamentioning
confidence: 99%